The acute effect of different frequencies of whole-body vibration on range of motion and jump performance in preadolescent karate athletes - Esra Atış; Suat Yıldız; Ertuğrul Gelen (Türk Spor ve Egzersiz Dergisi)
Whole-body vibration (WBV) treatments have acute effects on strength, power, and range of motion (ROM) by affecting the nerve-muscle function. However, there is little evidence about what could be the optimal practice for acute WBV. The purpose of this study is to reveal the acute effects of vibrations applied at different frequencies to preadolescent karate athletes on jump and ROM performance. Forty-six competing preadolescent karate athletes, who trained regularly (12.7 ± 1.7 years, 155.2 ± 3.1 cm, 50.9 ± 4.7 kg) and were blue belt and above, were included in the study. Each athlete followed a vibration protocol with four different frequencies (0, 25, 30, and 35 Hz) in random order on nonconsecutive days. After a 5 min light-paced warm-up jog before each protocol, three repetitions of 20 sec (20 sec rest between repetitions) vibration treatments were applied. Jump and ROM tests were carried out after each vibration treatment. Vibration protocols were compared in repeated measurements using the ANOVA and post-hoc methods. Based on the test results, a vibration frequency range of 30 to 35 Hz positively affected the countermovement jump, while the 30 Hz frequency range positively affected squat jumps. Furthermore, frequency ranges of 25, 30, and 35 Hz positively affected the ROM. This effect was most intensely revealed in the 35 Hz frequency range. Applying vibrations between the ranges of 30-35 Hz on preadolescent karate practitioners is believed to acutely improve both jump and ROM performance.